2021
DOI: 10.35675/befdergi.781416
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarının Ortaokul Matematik Dersi Kazanımlarını Yenilenmiş Bloom Taksonomisine Yerleştirebilme ve Soru Yazabilme Becerileri

Abstract: Bu araştırmanın amacı, ilköğretim matematik öğretmeni adaylarının matematik öğretim programı kazanımlarını yenilenmiş Bloom taksonomisine göre analiz etmelerini ve taksonominin boyutlarına uygun soru hazırlayıp hazırlamadıklarını incelemektir. Bu çalışmada karma yöntem araştırması kullanılmıştır. Araştırmanın katılımcıları 2018-2019 eğitim-öğretim yılında 3. sınıfa devam eden 54 öğretmen adayıdır. 5-8. sınıflara ait 215 kazanım öğretmen adaylarının her birine dörderli şekilde dağıtılmıştır. Daha sonra öğretmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Similarly, Rahmatih et al (2020) found that the questions prepared by prospective primary teachers were predominantly low-level. It seems that prospective teachers are better equipped to identify and formulate questions corresponding to understand and apply Polat, 2021;Cumhur et al, 2018;Sebastian, 2020). The questions prepared by prospective primary teachers in Turkish and mathematics courses are mostly in the apply and understand levels of revised Bloom's taxonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rahmatih et al (2020) found that the questions prepared by prospective primary teachers were predominantly low-level. It seems that prospective teachers are better equipped to identify and formulate questions corresponding to understand and apply Polat, 2021;Cumhur et al, 2018;Sebastian, 2020). The questions prepared by prospective primary teachers in Turkish and mathematics courses are mostly in the apply and understand levels of revised Bloom's taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, various studies investigated pre-service teachers' question preparation skills in terms of revised Bloom's taxonomy. These investigations analyzed the questions prepared by prospective teachers across different disciplines: Turkish language (Aktaş, 2017;Eyüp, 2012), science (Koray et al, 2005;Özcan & Akcan, 2010), social studies (Mercan Işık, 2019), and mathematics (Altaylı Özgül & Polat, 2021;Öztürk, 2019;Sebastian, 2020). In the realm of primary school teaching, studies examined the questions prepared by primary teachers in science (Dindar & Demir, 2006), prospective teachers on fractions (Özçakır-Sümen & Karakaş, 2022), and different text types in Turkish language (Aktaş, 2017;Erdoğan & Erdoğan, 2018) through the lens of the revised Bloom's Taxonomy.…”
Section: Introductionmentioning
confidence: 99%